Associations between serum ferritin levels and gestational diabetes mellitus among a non-anemic population - Menglin Zhou; Liying Song; Yan Huang; Danqing Chen (BMC Pregnancy and Childbirth)
Abstract Background Studies have shown a strong correlation between excess iron and the development of gestational diabetes mellitus (GDM), though iron is an essential trace element during pregnancy. This study aims to investigate the precise relationship between iron storage levels during late pregnancy and the development of GDM, trying to find out ways to meet pregnant iron storage requirements and reduce GDM risk simultaneously. Methods A non-anemic population consisting of 9,512 healthy singleton pregnant women were included in this study. Serum ferritin (SF) levels during the second and third trimesters and other clinical information were retrospectively collected. Restricted cubic splines (RCS) were performed to examined the non-linear associations between SF level and the GDM incidence as well as blood glucose related indicators during the second trimester. Moreover, the association between the variation of HbA1c levels and the fluctuation of SF levels throughout the third trimester was also explored with the method of RCS. Results Overall, women with GDM had slightly higher median SF level than women without GDM 20.5 (13.3, 32.3) vs. 19.8 (12.9, 30.5), P = 0.017) in the second trimester. A U-shaped relationship between GDM risk and SF levels in the second trimester was established after accounting for other cofounding factors (P < 0.001 for nonlinearity). Both GDM and non-GMD women revealed a significant negative relationship between hemoglobin A1c (HbA1c) and SF levels (P < 0.001 for nonlinearity for both). The 1-hour post-glucose load plasma glucose showed a positive correlation tendency with SF levels (P = 0.748 for nonlinearity) in GDM women, while the relationship between these two variables was not obvious in non-GDM women (P = 0.045 for nonlinearity). Generally, the levels of HbA1c rose in the trimester, however, maintaining a high SF level throughout the third trimester would substantially increase the HbA1c level among GDM women with high SF levels (> 30ng/ml) in the second trimester (P < 0.001 for nonlinearity). Conclusions GDM might result from high or low SF levels during the second trimester. Iron supplementation during pregnancy should be administered judiciously based on blood glucose level and iron storage capacity to maintain the SF level within an appropriate range.